Tackling corruption in India: Can e-governance show the way? - Pardhasaradhi, Y (2011)
Much has been said and written about corruption the world over. Various strategies and mechanism to cope with this basic issue have been adopted, but with little sucess. Corruption become systemic in India,especially, when the licence-permit quota raj was a preferred option. Globalisation, in fact, spawned a new wave of corruption, albeit going by the name of corporate lobbying. This phenomenon is not entirely new, either for the country or its people. It is not that we are confronting the problem of corruption alone. We have to think of its other variants-crony capitalism, corporate favours, doling out land, water and energy and topping it up with tax holidays. These variants are subtle and their dynamics are hard to be understood by the common man and society. Also, these have taken a form of public policy that drives the national economy. In this context, this article tries to put into perspective the possibility of tackling corruption, at least partially, by adopting the process of e-governance and he structure of e-government. E-governance reduces discretion, thereby curbing some opportunities for arbitrary action. It increases chances of exposure by maintaining detailed data on transatctions, making it possible to track and link the corrupt with their wrongful acts. By making rules simpler and transparent, e-government emboldens cittizens to question illogical procedures and their arbitrary application. - Reproduced.
Keywords: E governance - India; Corruption - India; Corruption